Simulating human bodymotion - Liao, Kenny Chun Ming. (2010)
Modern manufacturing industry demands that products be designed for the comfort and accessibility of consumers as well as workplaces for the health and safety of employees. These designs should be constructed in a virtual world. Digital human models (DHM) are required for these virtual worlds for manufacturing designs from an ergonomic perspective.